The effect of current on coral growth form on selected area in East Coast and West Coast of Tioman Island - Ahmad, Zuhairi; Halid, Nor Hidayah; Kamarumtham, Kharina; Saad, Shahbudin; Khodzori, Mohd Fikri Akmal; Hanafiah, Muhammad Faiz; Yusof, Mohd Hamizan (2016)
Current is a prominent event in the ocean and one of the significant factors influencing structure of reef ecosystem. Each individual reef has its unique growth and the distribution is depending on the current in the particular localities. Interrelation between current and morphological response of coral was studied in selected location at Tioman Island. Acoustic Doppler current profiles (ADCP) was deployed to collect data of current speed and current direction with 10 minutes interval. MIKE 21 Flow model FM were used to model the hydrodynamic pattern of the study area. The model was calibrated using secondary field current data with reasonable R2 value of 0.6096. Using the calibrated model, the mean current speeds for two selected stations at the West coast of Tioman Island were 0.0455 m/s and 0.1793 m/s; while the mean current speed for two selected stations at the East coast of Tioman Island were 0.0410 m/s and 0.0529 m/s. Based on the coral life form distribution at the study area, the type of growth form on the west coast was dominated by Acropora branching coral and massive/submassive coral while the east coast was dominated by Acoropora branching coral and plate-like coral respectively. Different growth form of coral emerged in response to different current speed. This study showed that the distribution of coral growth form was influenced by current action.